Risk of colorectal cancer in patients with appendicitis over the age of 40 years. (5th December 2022) - Lee, Mei Sze; Thomas, Alben; Pearson, John F.; Purcell, Rachel; Frizelle, Francis; Glyn, Tamara
Abstract: Aim: Acute appendicitis in late adulthood is hypothesized to be associated with an increased risk of colorectal cancer (CRC). This study aimed to establish whether patients over the age of 40 years presenting with appendicitis had an increased risk of being diagnosed with CRC over the subsequent 3 years. Method: This is a retrospective review of patients aged 40 years and over presenting to Canterbury District Health Board with appendicitis from January 2010 to December 2015. Clinical details were obtained for these patients and cross‐referenced with the New Zealand Cancer Registry for the 3 years following diagnosis. The incidence ratio rate (IRR) and standardized incidence ratio (SIR) were calculated by establishing the incidence of CRC in this cohort and comparing it with the Canterbury population data. Results: A total of 1099 patients met the inclusion criteria. The majority (75%) underwent CT as part of their initial work‐up. The rate of colonoscopy increased with age from around 10% between 40 and 49 years to 27% for those 70 years and over. Eleven cases of CRC were identified, resulting in an IRR 2.35 (95% CI 1.17–4.21). The SIR for this population was 3.28 (95% CI 1.82–5.92). Conclusion: The rate of CRC is significantly increased compared with the background population in this cohort. The results of this study support luminal investigation of adults aged 40 years and over who present with acute appendicitis as CT alone was insufficient to detect the pathology.